2021
DOI: 10.1002/ehf2.13199
|View full text |Cite
|
Sign up to set email alerts
|

Worsening of heart failure by coronavirus disease 2019 is associated with high mortality

Abstract: Aims Patients with advanced heart failure (HF) with reduced left ventricular ejection fraction (HFrEF) and concurrent coronavirus disease 2019 (COVID-19) might have a higher risk of severe events. Methods and results We retrospectively studied 16 patients with advanced HFrEF who developed COVID-19 between 1 March and 29 May 2020. Follow-up lasted until 30 September. Ten patients previously hospitalized with decompensated HFrEF were infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Single‐centre and nationwide cohort studies showed that COVID‐19 affected referral and hospitalizations of patients with acute HF and that HF was associated with high mortality. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 Yet, the impact of COVID‐19 on HF patients and vice versa the relevance of HF events during COVID‐19 in a multicentre international cohort is unknown. 19 , 20 Therefore, the Postgraduate Course in Heart Failure (PCHF) group built an international multicentre registry for hospitalized COVID‐19 patients with CV diseases and/or risk factors (CVDRF).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single‐centre and nationwide cohort studies showed that COVID‐19 affected referral and hospitalizations of patients with acute HF and that HF was associated with high mortality. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 Yet, the impact of COVID‐19 on HF patients and vice versa the relevance of HF events during COVID‐19 in a multicentre international cohort is unknown. 19 , 20 Therefore, the Postgraduate Course in Heart Failure (PCHF) group built an international multicentre registry for hospitalized COVID‐19 patients with CV diseases and/or risk factors (CVDRF).…”
Section: Introductionmentioning
confidence: 99%
“…An impaired prognosis can be expected in patients requiring hospitalization with COVID‐19 diagnosis. Single‐centre and nationwide cohort studies showed that COVID‐19 affected referral and hospitalizations of patients with acute HF and that HF was associated with high mortality 9–18 . Yet, the impact of COVID‐19 on HF patients and vice versa the relevance of HF events during COVID‐19 in a multicentre international cohort is unknown 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…However, and not unexpectedly, mortality was dramatically increased at the 6-month follow-up. Interestingly, patients with advanced CHF with clinical deterioration following SARS-CoV-2 infection do not necessarily develop fever or other signs consistent with acute infection syndrome, thus suggesting that acute decompensation of CHF can be caused by COVID-19 in a region with high transmissibility of SARS-CoV-2 ( 42 ).…”
Section: Cardiovascular Diseases Managementmentioning
confidence: 99%
“…COVID-19 can damage cardiovascular system in several ways, including systemic inflammation, endothelial dysfunction, hypoxemia, micro and macrovascular thrombi formation as well as thromboembolic complications are frequent, and 36% patients hospitalized for COVID-19 developed myocardial injury [38 ▪ ]. COVID-19 has been associated with several disorders complicated by CS including fulminant myocarditis [39 ▪ ], heart failure decompensation [40 ▪ ,41], Tako-Tsubo syndrome [42 ▪ ], arrhythmias [43], thromboembolic events [44 ▪▪ ] and right ventricular failure in COVID-19 respiratory failure [45 ▪ ]. There are also important differences in the management of CS in the setting of COVID-19 infection [37 ▪ ].…”
Section: Coronavirus Disease 2019 and Cardiogenic Shockmentioning
confidence: 99%